Therapy focused on schemes: conceptualization and research (Archives of Clinical Psychiatry, 2008)
BACKGROUND: The aim of the present study was to review the studies conducted on the Therapy Focused on Schemes and on the Young Schema Questionnaire. OBJECTIVES: To find out the recent studies, to evaluate the Young Schema Questionnaire and identify the research centers more involved in scientific production related to this model. METHODS: The articles published in databases during/from the period of 1998 to 2007 were reviewed. The keywords used were "Young Schema Questionnaire", "YSQ", "Schema Questionnaire", "Survey of Schemes" and "Focused on Therapy Schemes". Nine articles were selected for having established the focus in addressing the schemes approach. RESULTS: It was possible to verify that the research centers on this field are nowadays spread in four of the five continents - America, Europe, Asia and Oceania. It was found that psychometrics properties were significant at the internal consistency of scale and regarding to indices of being a reliable and valid measure, considering the differences between clinical and non-clinical groups. DISCUSSION: In general, the results related to the Young Schema Questionnaire have demonstrated that it is an important measure available to the mental health professionals for uses it in clinical as well as research settings.